Improving Performance Of Health Workers In Batam City: Through Authentic Leadership And Servant Leadership - Muhammad Arief El Habibie; Etty Sri Wahyuni; Diana Titik Windayati (International Forum of Researchers and Lecturers, 2025)
The purpose of this research is to know and analyze the influence of authentic leadership and servant leadership partially and simultaneously on performance of health workers in Batam City. The method used in this research uses a method, namely the type of research used in this research is a quantitative research method. This research uses an analytical tool is SPSS Version 23. The population in this study is all health workers spread across Batam City whose numbers cannot be known and recorded with certainty. The sampling method in this study used accidental sampling technique. By using the Zikmund formula, the final sample size used was 100 people. The results of this research are (1) Authentic leadership partially has a positive and significant effect on performance of health workers, (2) Servant leadership partially has a positive and significant effect on performance of health workers (3) Authentic leadership and servant leadership together or simultaneously have a positive effect and significant to the performance of health workers. The coefficient of determination (adjusted R square) is 0.669 or equal to 66.9%. This figure means that the independent variables consisting of authentic leadership and servant leadership affect performance of health workers variable while the remaining 29.1% of the performance of health workers variable is influenced by other variables not examined in this study